Ayurvedic Management of Dushtavrana (Non-Healing Ulcer)– A Case Report: Pharmaceutical Science-Pharmacology - Nycy, Dr.B. S; Rajkumar Gupta, Dr.; Twinkle Joshi, Dr.; Priyal Bansal, Dr. (International Journal of Life Science and Pharma Research, 2023)
Treatment of non-healing ulcers (dushtaVrana) is a clinical challenge. Even though contemporary medicine can manage infected wounds through antibiotics, non-healing wounds are still a problem to be solved. Ayurveda contributes significantly in the management of dushtavrana through its holistic approach. This case report discusses a 52-year-old male patient who complained of a non-healing ulcer over the left big toe’s metatarsophalangeal joint area for six months. With associate complains of pricking pain and itching in the nearby area of the ulcer. Cleaning of the ulcer was done with Nomura arka (Distillation preparation of cow urine) followed by Dhara (wash) with kwatha prepared out of lodhra(SymplocosracemosaRoxb), yashtimadhu (Glycyrrhizaglabra), manjishta (Rubiacordifolia).Sadhyovirechana (Purgation therapy) is performed with trivrutlehua and milk. Orally Aragwadhadikashaya, Sarivadhyasava, and Guggulupanchapalachurna were administered. After 15 days of treatment, there was considerable relief in the pain, and the wound started healing. One month of treatment led to the complete healing of the wound. Parisheka of lodra, yashtimadhu, and manjishtakwatha helps clean and heal the wound due to its vranahara, sandhaneeyaaction. Virechana with Trivrutlehya helps in the elimination of vitiated pitta, which allows for enhancing wound healing. Aragwadhadikashayam helps in dushtaVranashodhana and reduces the itching.Sarivadhyasavaisamapachaka, pittahara and pidakahara.GuggulupanchapalachurnacontainsGuggulu, Pippali, Triphala, etc. as its contents. Hence it contributes to the management of pain and healing of the ulcer.